Successful Treatment of Early Endometrial Carcinoma by Local Delivery of Levonorgestrel: A Case Report - D. Wildemeersch; E. Anderson; K. Lambein; P. Pauwels; M. Dhont (Hindawi Limited, 2010)
We describe a case of a 67-year-old Caucasian woman with an early, moderately-differentiated adenocarcinoma of the endometrium. A levonorgestrel-releasing intrauterine system was inserted, which she tolerated well. A full D&C, following removal of the device, was performed after 9 months, confirming absence of tumoral tissue. Examination after 24 months showed a very thin endometrium, indicating complete remission.